TAX SOVEREIGNTY: STATE RESISTANCE STRATEGY FOR MAINTAINING MARKET STABILITY AND NEOLIBERALISM IMPACT IN INDONESIA - Zainal Fadri (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractNeoliberalism developed rapidly in developing countries as a form of the implications of post-independence capital needs. Indonesia as a developing country is not immune from the influence of neoliberalism that leads into the world market and trade system, so that the country becomes quite weak in regulating existing economic patterns because of its dependence on capital-giving countries in the form of investment and control of strategic economic sectors. The method used is descriptive qualitative by searching manuscripts and literature about the influence of the market on the welfare of citizens and is equipped with materials regarding tax and sovereignty for the state. The results obtain that tax is a form of state resilience and firmness in suppressing hyper-exploitative market developments with the aim of welfare for all citizens. Taxes are used as a form of investor resistance in managing the economy with the hope of creating a regulation which can control the country's economy.Keywords: tax sovereignty; state; market; neoliberalismAbstrakNeoliberalisme bekembang secara pesat di negara-negara sedang berkembang sebagai bentuk implikasi dari kebutuhan modal pasca kemerdekaan. Indonesia sebagai negara sedang berkembang tidak luput dari pengaruh neoliberalisme yang menuntun masuk ke dalam sistem pasar dan perdagangan dunia, sehingga negara menjadi lemah dalam mengatur pola perekonomian yang ada karena ketergantungan atas negara-negara pemberi modal dengan bentuk investasi dan menguasai sektor-sektor perekonomian strategis. Metode yang digunakan adalah deskriptif kualitatif dengan penelusuran naskah serta literatur mengenai pengaruh pasar terhadap kesejahteraan warga negara dan dilengkapi bahan-bahan mengenai pajak dan kedaulatan pajak bagi negara. Hasil yang didapatkan bahwa pajak merupakan suatu bentuk ketahanan dan ketegasan negara dalam menekan perkembangan pasar secara hipereksploitatif dengan tujuan kesejahteraan bagi seluruh warga negara. Pajak digunakan sebagai bentuk perlawanan investor dalam mengelola perekonomian dengan harapan terciptanya suatu regulasi yang dapat mengendalikan perekonomian negara.Kata kunci: Kedaulatan Pajak; Negara; Pasar; Neoliberalisme